Designing Business Process For User Persona Determination and Client Ordering Using Business Process Reengineering Method - Nafisa, Munalys; Lalu, Heriyono; Salma, Sheila Amalia (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
Kliktrip is an online-based travel agent that was founded in 2018 with products being marketed, namely trips & activities. The OTA (Online Travel Agent) business always increasingly growing year by year, but because tourism conditions have begun to change since the Covid-19 pandemic, Kliktrip sales have decreased from 2020 to the present. This degradation in sales is due to changes in the behavior of Kliktrip consumers, gonverment regulation and other external factors that changes the need of using OTA which originally required OTA for weekend trip with family, turned into requiring OTA for office or business purposes. However, Kliktrip has not made changes to new products and business processes to meet consumer needs after the Covid-19 pandemic. This research uses Business Process Reengineering to carried out the form of a new business process that is relevant to Kliktrip conditions, so that Kliktrip can adapt quickly in the face of changes in environmental conditions during the Covid-19 pandemic.